Asian Capital Market Integration: Theory and Evidence - Cyn-Young Park (Asian Development Bank (ADB), 2013)
Financial integration is a multidimensional process through which allocation of financial assets becomes increasingly borderless. This paper assesses the progress achieved thus far in capital market integration in Asia, and compares regional capital market integration with global financial integration. The results of the analysis on which the paper is based indicate that while the pace of regional integration of financial markets in Asia's emerging economies has accelerated in recent years, these markets remain more integrated with global financial markets than with other financial markets in the region. Further, integration of the region's domestic local-currency bond markets with their regional and global counterparts lags the pace of integration of its equity markets. The study also assesses the degree to which volatility in equity- and bond-market returns driven by financial turmoil originating at both the regional and global levels spills over into emerging Asia domestic equity and bond markets. The results of this analysis indicate that such spill-over significantly impacts both domestic equity and bond markets in the region. This finding suggests that ongoing regional capital market integration initiatives should take into account the risk of contagion that regional financial integration presents, and introduce measures for mitigating such risk as a means of ensuring financial stability in the region.
hdl:11540/2313
Keywords: F30; F36; G15; 330; capital markets; emerging Asia; regional financial integration